Response of midland sorghum varieties to different intra-row spacing at kaffa zone south western Ethiopia - Abriham, Ashenafi (International Journal of Agricultural Research, Innovation and Technology, 2023)
The experiment was conducted to determine optimum plant spacing and suitable variety and as well as to identify the interaction effect of varieties and Intra-row spacing on the yield of sorghum. The experiment having a factorial arrangement of three varieties (Geremew, Lalo and farmer’s local variety) and three intra-row levels (10 cm, 15 cm and 20 cm) was laid out in randomized complete block design (RCBD) with three replications. According to the current results, varieties were significantly (p<0.05) affected by all the parameters (days to maturity, plant height, panicle length, thousand seed weight and total grain yield) except stand count. The maximum days to maturity and total grain yield (205.2 days and 5628.1 kg ha-1 respectively) were obtained from Lalo. The highest thousand seed weight (23.1 g) was recorded from Geremew and at it takes a short period for maturity (119.5 days). Similarly, intra-row spacing significantly (p<0.05) affected the panicle length and stand count. The highest panicle length (28.15 cm) was recorded in 15 cm intra-row spaced plants. The maximum stand count (78.6 % and 83.6%) was obtained from 15 cm and 20 cm spaced plants respectively. Generally, the outcome of this study revealed that even though the yield was statistically non-significant to intra-raw spacing, at 15cm and 20cm the grain yield was a maximum of 4178.5 kg ha-1 and 4190.9 kg ha-1, respectively. Therefore, among the intra-row spacing 20 cm intra-row spacing for its minimized planting materials (seed) and easy management and among the varieties, Lalo could be promoted in study areas and similar agro-ecologies. Int. J. Agril. Res. Innov. Tech. 12(2): 138-143, December 2022